The song of Sourwood Mountain [large type] - Gabhart, Ann H., 1947- (Center Point Large Print, 2024)
"While the century began with such promise, it is 1910 when Mira Dean's hopes of being a wife and mother are dashed to pieces. Her fiancé dead from tuberculosis, Mira resigns herself to being a spinster schoolteacher -- until Gordon Covington shows up. No longer the boy she knew from school, Gordon is now a preacher who is full of surprises. First, he asks Mira to come to Sourwood in eastern Kentucky to teach at his mission school. Second, he asks her to marry him. Just like that. And all at once the doors that had seemed firmly shut begin to open, just a crack. With much trepidation, Mira steps out in faith into a life she never imagined, in a place filled with its own special challenges, to serve a people who will end up becoming the family she always dreamed of."--